Hubungan Antara Dukungan Keluarga Dengan Tingkat Kecemasan Pasien Praoperasi di Ruang Bedah Kelas III Rumah Sakit Umum Daerah 45 Kuningan - Herlina, Lili (Jurnal Ilmu Kesehatan Bhakti Husada: Health Sciences Journal, 2012)
Introduction:. Method: This study is designed by quasi-experimental research design with pre-test and post-test control group design. The subject consist 48 people who meet the inclusion criteria. Research subjects were divided into 2 groups: 24 persons as the treatment group and 24 others as the control group. The research data is analyzed by MANAVA test (multivariate analysis) using the least significance difference. Results: The results showed there were highly significant differences (p=0,000) between the average systolic blood pressure/diastolic in the group treated with the control group. Likewise there is a very significant difference (p=0,000) on average systolic blood pressure/diastolic between the various treatment groups to-1 to treatment to-6 with a maximum of 11 mm Hg reduction in systolic pressure and 14.8 mm Hg in diastolic pressure. Discussion: Nurses can promote laughter therapy as part of lifestyle modification or non-pharmacologic therapy for patients with hypertension, especially patients with mild hypertension and may consider laughing become a therapy remains one of the procedures in the management of mild hypertension in the health center.